Quantitative analysis of PACAP-38 and amyloid beta composition using a dual reaction in reduced graphene oxide biosensor to verify the neuroprotective role of PACAP-38 - Lee, Seungjun; Song, Hyo Ryeong; Park, Keunwan; Lee, Minhyeong; Lee, A-Hyeon; Roh, Seung Min; Park, Yejin; Kim, Hye Jin; Kwon, Youngeun; Yang, Seung-Hoon; Kim, Jinsik (Elsevier BV, 2022)
Here, we developed a sophisticated reduced graphene oxide (rGO) sensor capable of monitoring the progress of Alzheimer's disease by quantifying the concentration of amyloid beta (A beta) and pituitary adenylate cyclase activating polypeptide 38 (PACAP-38). Western blot analysis following induction of apoptosis in mouse hippocampal neurons with TNF-alpha demonstrated that PACAP-38/A beta binding inhibited neural cell apoptosis. To verify the direct binding of PACAP-38 to A beta, a simulated docking model was generated, and binding affinities were quantified using surface plasmon resonance (SPR). After PACAP-38-A beta binding was confirmed, the properties of each protein were evaluated by the rGO sensor based on differences in their charge to determine the PACAP-38: A beta ratio. Based on the observed changes in resistance obtained by measuring each protein monomer, expected resistance change values were derived for each binding reaction and subsequent accumulation of PACAP-38 and A beta. Subsequently, rGO sensor measured changes in resistance following binding and accumulation of each protein. The resistance change values were compared with the expected values to verify the accuracy of the sensor for quantifying accumulated proteins. The accuracy of the sensor was determined based on deviation of the sensor output within its dynamic range. The significance was expressed based on the equation for significance values and was confirmed to be as high as 96% between expected and measured values. Collectively, our results verify the neuroprotective role of PACAP-38 and proposes rGO sensor as a potential tool for early diagnosis of as well as monitoring the progression of Alzheimer's disease.